Implementasi Teori Hukum Keadilan Bermartabat Dalam Hukum Investasi - Christina Angelita (Kertha Wicaksana, 2024)
Investment plays a crucial role in the economic development of a nation and the welfare of its people. Investment law governs the norms and regulations that encompass the possibilities, requirements, protections, and directions of investment to achieve such welfare. In the context of Indonesia, economic development and societal well-being are regulated by the Constitution, with the government having legislation that regulates both domestic and foreign investment. The theory of dignified justice, based on the values of Pancasila, serves as a fundamental principle in investment law, aiming for absolute justice, fair certainty, and utility as primary objectives. A case study on investment fraud in the mining sector illustrates the application of dignified justice theory in legal practice. This research aims to analyze the implementation of dignified justice theory in investment law in Indonesia, focusing on the principles of investment and case studies of investment fraud. The research method employed is juridical normative and literature review. The findings demonstrate that dignified justice serves as the main guideline in upholding the law and providing certainty for economic actors. Dignified justice reflects how the law addresses injustice, with the hope that existing regulations ensure fair certainty for all parties. Thus, investment law in Indonesia embraces the principle of dignified justice to bring about shared prosperity within society.